2015
DOI: 10.1186/s40814-015-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

Timed walk as primary outcome measure of treatment response in clinical trials for HTLV-1-associated myelopathy: a feasibility study

Abstract: BackgroundTo advance the treatment of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), randomised controlled therapeutic studies with appropriate and sensitive outcomes are reuired. One candidate outcome is the 10-metre walk test (10MWT), a patient-centred, simple and functional measure. To calculate sample size based on 10MWT as the primary outcome, variability within and between subjects must be known.MethodsData on 10MWT from 76 patients with HAM/TSP were prospectively collected from fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
1
4
1
Order By: Relevance
“…In the present study, it was observed that patients with HAM/ TSP were female, older than 40 years, and with necessity of some aid for locomotion. These findings are consistent with the sociodemographic and clinical profile found in previous studies 5,7,8,12 . Some authors suggest that many patients with symptomatic HAM/TSP may even require wheelchairs 12,14 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, it was observed that patients with HAM/ TSP were female, older than 40 years, and with necessity of some aid for locomotion. These findings are consistent with the sociodemographic and clinical profile found in previous studies 5,7,8,12 . Some authors suggest that many patients with symptomatic HAM/TSP may even require wheelchairs 12,14 .…”
Section: Discussionsupporting
confidence: 92%
“…Human T-cell lymphotropic virus type-1 (HTLV-1)associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a neurological disorder caused by demyelination and axonal destruction of the spinal cord [1][2][3] . This health condition is more prevalent in women older than 40 years of age [2][3][4][5][6][7][8] . Patients with HAM/TSP have motor, sensory, and autonomic alterations, which may influence gait performance, balance maintenance, and functional mobility [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 10 mWT is a simple and reliable outcome measure for HAM with a minimal burden on patients. Next, the 10 mWT of the placebo group improved, which was contrary to the results of clinical observations [28]. Thus, the placebo effect is nonnegligible in clinical trials on HAM.…”
Section: Discussioncontrasting
confidence: 64%
“…In slow progressors, we used 10 mWT as the primary outcome because it is a sensitive and objective functional measure with small intra-patient variability, and it can worsen by an average of 5.74% per 6 months in untreated patients with HAM [28]. Based on our clinical experience, there was an improvement of approximately 15% per 6 months with prednisolone (unpublished data), which is roughly equivalent to 2 years worth of gait deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observational studies, it is confirmed that the main problems that affect these patients involve disorders of gait 21,22,8,23 , balance 24,25,26 , pelvic floor 27,28 spasticity 29,30 and pain 10,31,32,33 . These dysfunctions affect daily life activities 5,34 and quality of life 35 .…”
Section: Discussionmentioning
confidence: 93%